1971
DOI: 10.1002/cber.19711041120
|View full text |Cite
|
Sign up to set email alerts
|

Zur Konfiguration der Jaborosalactone, ein neuer Abbauweg für Withanolide

Abstract: rn Die 14a.17c(H.20S-Konfiguration der Jaborosalactone wurde durch Verknupfung von Jaborosalacton D (4a) mit bekannten Steroiden bewiesen. Es wurde em neuer WithanolidAbbau entwickelt, dessen entscheidende Schritte die Reduktion von 6 zu 7, die Hydrogenolyse von 9 und die AtheroEnung bei 15 sind. On the Configuration of the Jaborosalactones I), a New Degradation Scheme for WithanolidesThe 14a.17ctH.20S-configuration in the Jaborosalactoiies was demonstrated by the dcgradation of Jaborosalactone D ( 4 4 to know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The immunosuppressive activity of withaferin A is evident from its ability to inhibit adjuvant arthritis in rats and the graft versus host reaction in chicks (251). Similar activity was also shown by withanolide D (68). The immunosuppressive effect of Lycium substance A (5) was demonstrated by BAHRand HANSEL (252) who studied its ability to inhibit proliferation of murine spleen cell cultures.…”
Section: Biological Activity Of Withasteroidsmentioning
confidence: 61%
See 1 more Smart Citation
“…The immunosuppressive activity of withaferin A is evident from its ability to inhibit adjuvant arthritis in rats and the graft versus host reaction in chicks (251). Similar activity was also shown by withanolide D (68). The immunosuppressive effect of Lycium substance A (5) was demonstrated by BAHRand HANSEL (252) who studied its ability to inhibit proliferation of murine spleen cell cultures.…”
Section: Biological Activity Of Withasteroidsmentioning
confidence: 61%
“…Attempts to introduce 17J3-hydroxyl group by addition of appro- References pp. [93][94][95][96][97][98][99][100][101][102][103][104][105][106] Since syntheses of various other withanolides have been discussed by GLOTTER in a recent review (J 3), the present article provides only an outline of the synthesis ofphysalolactone B (55) and withanolide D (68) in Charts 8 and 9, respectively.…”
Section: Synthesis Of Withanolidesmentioning
confidence: 99%
“…Jaborosalactone U [4] had *Hand 13C-nmr data markedly different from the previous compounds but closely resembling those of trechonolide A [5] for rings A-D (10). The 13C-nmr spectra showed the presence of only two sp2 carbons which corresponded to C-2 and C-3.…”
mentioning
confidence: 62%
“…Further, three rotamers around the C-22-C-23 bond are possible in each case; thus, the twelve structures were generated and their geometry optimized by molecular modeling using the AMI semiempirical method. NOESY experiments carried out on jaborosalactone U [4], showed that at short mixing times (0.7 sec) extremely weak or no nOe cross-peaks were observed between protons over 3.0 Á apart. Under these conditions, strong cross-peaks were observed for the pairs H-28/H-23, H-21/H-23, H-28/H-22, and H-21/H-22 (Table 2).…”
mentioning
confidence: 97%
See 1 more Smart Citation